Fitness of a high-calcium slag for the production of alkali activated materials. - Pavia, Sara (ISBN: 978-989-54499-1-0, 2021)
Alkali-activated (AA) materials are considered a more sustainable alternative to some traditional materials. This paper studies the feasibility of producing building materials by activating an Irish ground granulated blast furnace slag (GGBS) with a range of alkali metal activators. The results indicate that the GGBS can be successfully used for the production of AA materials. The slag is ultra-fine, basic and highly amorphous, with CaO/SiO2 and Al2O3/SiO2 ratios that are considered suitable for alkali-activation. The chemical composition complies with the standard requirements for the use of slags in concretes, mortars and grouts. The slag is totally amorphous, hence devitrification was required to determine its mineral composition. Devitrification evidenced that the composition concurs with that of other active slags (a melilite-gehlenite isomorphous solution) indicating a high reactivity. Cracking due to drying shrinkage is one of the challenges of AA materials, but the high Ca content of the Irish slag has likely reduced drying-shrinkage cracking, providing a generally sound microstructure. The thermal tests results support the chemical and mineralogical analyses indicating that the GGBS has neither organic carbon nor carbonates. In addition, the heat evolution in the calorimetric tests mirrors the evolution of the glass and the crystalline phases determined with X-ray diffraction on devitrification. It is clear that most of the glass becomes crystalline between 500 and 800°C, and that the steady heat absorbed in this segment (endothermic curve) is due to the decomposition of the glass to form merwinite and gehlenite. The slag was activated with sodium hydroxide (NaOH), and sodium silicate (Na2SiO3), both combined and separately, to produce mortars. The mortars obtained show reasonable setting times and minimal loss of workability. The strengths are lower than those in the literature, however, the Na2SiO3+NaOH activated GGBS shows values suitable for a wide range of applications. The main reason for the strength loss when using the Na2SiO3 activator is mainly an excessive %Na2O by mass of slag, while the reason for the strength loss when the NaOH activator is involved is an elevated alkalinity. The strength results and the microstructural analyses evidenced that rising curing temperature improves the microstructure and the mechanical properties of the Na2SiO3+NaOH activated GGBS. It seems from the results, that the GGBS analysed is too fine for a successful activation with Na2SiO3 alone, and too reactive for high alkali hydroxide concentrations. The best activator is likely a combination of Na2SiO3 and a low molarity (<6M) alkali hydroxide.
CEES 2021 - International Conference on Construction, Energy, Environment and Sustainability.
PUBLISHED
Coimbra, Portugal
Keywords: Ground Granulated Blastfurnace Slag (GGBS); Alkali activation; Devitrification; Amorphousness; Strength